The glaciers of Iceland a historical, cultural and scientific overview - Helgi Björnsson 1942- (Atlantis Press, 2017)
This book is the result of years of research by Helgi Björnsson and his colleagues at the University of Iceland and elsewhere. It gives a detailed account of glaciers of Iceland and glaciers in the lives of Icelanders. Cultural perspective on these now fading giants.
Keywords: Geologie; Gletscher; Island; Glaciers / Iceland; Geology / Iceland; Natural history / Iceland; Geology; Glaciers